2015
DOI: 10.1111/ijn.12416
|View full text |Cite
|
Sign up to set email alerts
|

Perceived organizational support and intention to remain: The mediating roles of career success and self‐esteem

Abstract: The aim of this study was to explore the relationships among perceived organizational support, career success, self-esteem and intention to remain. A cross-sectional study was designed, and subjects were recruited from six nonprofit organizations in China in spring 2015. A convenience sample of 610 nurses answered a survey with questions related to their ideas about their work. Structural equation modelling analyses were conducted. The results revealed that perceived organizational support was positively assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
69
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(75 citation statements)
references
References 53 publications
(75 reference statements)
6
69
0
Order By: Relevance
“…Furthermore, a higher level of POS positively related to work engagement and organizational citizenship behavior and contributed to innovative behaviors in nurses (Ko et al., 2015 and autonomy . A higher POS can therefore increase the intentions in the nurse …”
Section: Review Of Literaturementioning
confidence: 96%
See 1 more Smart Citation
“…Furthermore, a higher level of POS positively related to work engagement and organizational citizenship behavior and contributed to innovative behaviors in nurses (Ko et al., 2015 and autonomy . A higher POS can therefore increase the intentions in the nurse …”
Section: Review Of Literaturementioning
confidence: 96%
“…There is a plethora of evidence around the world linking higher POS to nurses’ job outcomes such as job satisfaction, competence, job engagement, innovative behaviors, intention to stay, and burnout . However, it can be noted that there is a paucity of literature examining organizational support perceptions in nurses in relations to job autonomy and work commitment .…”
Section: Review Of Literaturementioning
confidence: 99%
“…Another study examining intent to stay surveyed nurses working in long‐term care homes and found similar results (McGilton et al., ). Liu and Liu () and Mrayyan () conducted survey‐based studies examining intent to stay in nonspecialty nurses who had been practising for a year or less and found perceived organizational culture, job satisfaction and leadership support as influencing factors. Most of the existing literature concerning both turnover and intent to stay focused on newer nurses working in generalized practice areas.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…If nurses perceive the support of the organization and feel that they are accepted by the organization, they will be motivated to devote themselves to work and care about the development of the organization. Therefore, they probably do not look for other employment opportunities and stay in the current position (Liu & Liu, ). Previous research has indicated that perceived organizational support plays an important role in ITS (Gao, Newcombe, Tilse, Wilson, & Tuckett, ; Li et al, ).…”
Section: Introductionmentioning
confidence: 99%